SOCIAL PERSPECTIVE OF COLORS: रंगो का सामाजिक परिप्रेक्ष्य - Dev, Sandhya (International Journal of Research -GRANTHAALAYAH, 2014)
Color is a symbol of joy and enthusiasm. Colors have a special effect on the human brain. Colors produce attractiveness and vividness in any object. The source of color is light. Identification of different colors is possible because objects reflect light and reflect it. Light enters the eyes. Acts on our vision sensation. Due to this, the sensation of light is produced and the brain feels color. Generally, objects reflect some part of the light and some part absorb it. Eg 0 if the objects are green. So she charms all colors except Hare. The object that appears white reflects all colors. Black objects corroborate all colors. रंग आनंद एवं उत्साह का प्रतीक है। रंगों का मानव मस्तिष्क पर विशेष प्रभाव पड़ता है। रंग किसी भी वस्तु में आकर्षकता एवं वोधगम्यता उत्पन्न करते है। रंग की प्राप्ति का स्त्रोत प्रकाश है। विभिन्न रंगो की पहचान इसीलिए संभव होती है क्योंकि वस्तुएं प्रकाश को परावर्तित यो अभिशोषित करती है। प्रकाश आंखो में प्रवेश करता है। हमारी दृष्टि संवेदना पर क्रिया करता है। इसके कारण प्रकाश की संवेदना उत्पन्न होती है और मस्तिष्क को रंग की अनुभूति होती है। सामान्यतः वस्तुएं प्रकाश का कुछ भाग परावर्तित एवं कुछ भाग अभिशोषित करती है। उदा0 यदि वस्तुएॅ हरे रंग की है। तो वह हरे के अलावा सभी रंगो को अभिशोषित करती हैं। जो वस्तु सफेद दिखाई देती है वह सभी रंगो को परावर्तित करती है। काली वस्तुएं सभी रंगो को अभिशोषित करती है।